Circulating microRNAs as dynamic biomarkers of response to treatment with FOLFIRINOX combination therapy in advanced pancreatic ductal adenocarcinoma. (23rd February 2017) - Meijer, Laura L; Frampton, Adam E; Garajová, Ingrid; Caparello, Chiara; Le Large, Tessa Y S; Funel, Niccola; Vasile, Enrico; Stebbing, Justin; Krell, Jonathan; Kazemier, Geert; Giovannetti, Elisa
Abstract: Background: Advanced pancreatic ductal adenocarcinoma remains a clinical challenge. Only a third of patients receiving FOLFIRINOX combination chemotherapy displays tumour downstaging. Because of their high stability in plasma, especially in extracellular vesicles, microRNAs (miRNAs) hold great promise as a new class of minimally invasive biomarkers. Our aim was to identify differently expressed, blood-based miRNAs to select and monitor patients with advanced pancreatic ductal adenocarcinoma who would benefit from FOLFIRINOX. Methods: In this prospective, multicentre study, we enrolled 50 patients with locally advanced or metastatic pancreatic ductal adenocarcinoma receiving FOLFIRINOX. The first cohort of 11 patients was selected according to their short versus long progression-free survival, and miRNA profiling was performed to identify differentially expressed circulating-free miRNAs. Emerging miRNAs, as well as various endogenous control miRNAs, were then validated in extracellular vesicles by RT-PCR in a second cohort of 16 non-progressive patients (ie, those with partial response or stable disease). No further analyses were performed in the other 23 patients, who included progressive patients or those without samples available for exosomes extraction. Findings: MiR-29a emerged as a potential biomarker both in the profiling and RT-PCR analyses, in the first and second cohorts, respectively. In particular, it was significantly upregulated (2·36-fold change, p=0·0024) in extracellular vesicles after five cycles of FOLFIRINOX therapy in non-progressive disease. Interestingly, the expression of miR-29a was significantly higher in extracellular vesicles than in circulating free miR-29a (p<0·0001). In addition, three miRNAs were considered to be normalising miRNAs; miR-93 showed the most stable expression and was chosen as an endogenous control. Interpretation: We show that altered levels of miR-29a in plasma extracellular vesicles can anticipate progression of pancreatic ductal adenocarcinoma and guide therapeutic options. Higher miR-29a expression in extracellular vesicles than in circulating free miR-29a suggests an active secretion and warrants further studies on its role in tumour–host interactions. These findings open new opportunities to explore blood-based miRNA profiles and specific miRNA candidates to select patients most likely to respond to FOLFIRINOX. Funding: Bennink Foundation, Netherlands; Cancer Center Amsterdam Foundation, Netherlands; AIRC Grant Start Up, Italy; FAS grant, Italy; Action Against Cancer, UK; No Surrender Cancer Trust (in memory of Jason Boas), UK.